Senam aerobik dan konsumsi zat gizi serta pengaruhnya terhadap kadar kolesterol total darah wanita - Siti Fatimah; Apoina Kartini (Jurnal Gizi Klinik Indonesia, 2011)
Background: Hypercholesterolemia is a condition in which levels of cholesterol in the blood above normal levels (≥ 240 mg/dl). Physical exercises done regularly useful in the regulation of cholesterol, is total cholesterol, LDL cholesterol and triglycerides in the blood decreased, while HDL cholesterol increased. Food has an important role in association with the incident hypercholesterolemia.Objective: The purpose of this study was to determine the effect of aerobic exercise on blood total cholesterol level of adult women in the city of Semarang.Method: This research was explanatory research with cross sectional study. Subject was women aged 20-49 years gymnastic participants, as a comparison group was a housewife who was not doing gymnastics. Twenty three samples for group2 by matching on nutritional status and age and with the sampling purposive sampling. Adequacy levels of carbohydrates, proteins, fats, and also vitamins A and C were obtained through 2x24-hour recall was not a sequence, and processed using NutriSurvey. Results of independent t-test used to determine the effect of cholesterol levels between groups, and chi square test was used to determine association with nutrient adequacy levels of total cholesterol.Results: The results showed no significant difference in mean total cholesterol level between groups of gymnastic participants (201.2 g/dl) with housewife group (208.3 g/dl). Housewife group was belonging to hypercholesterolemia by 52.2%, while in group of exercise participants at 43.5%. Sufficiency level of protein showed a role in the total cholesterol level of adult women.Conclusion: The aerobic gymnastics did not affect total cholesterol. Moderate level of protein adequacy contributes to the total cholesterol level of adult women.